Pedagogi kritis materi teks deskripsi pada buku teks bahasa Indonesia fase F (analisis wacana kritis) - Harsaid, Yogo; Anwar, Miftahulkhairah; Rohman, Saifur (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Based on Regulation of the Minister of Education and Culture of the Republic Indonesia Number 22 of 2022 concerning the Strategic Plan of the Ministry of Education and Culture must be translated into textbook teaching resources. The materials in the Indonesian language textbook phase F must apply with a critical perspective or critical pedagogy, as a manifestation of the mandate of the minister of education and culture. Descriptive text material is material where elements of critical pedagogy can be seen. The aim of this research is to look at the elements of critical pedagogy, as well as to see how critical pedagogy is presented in descriptive text material in Indonesian textbooks. This research uses Norman Fairclough’s critical discourse analysis research method. Norman Fairclough’s Critical Discourse Analysis divides it into three dimensions, namely the text dimensions, discourse practice dimensions, and the sociocultural dimensions. The research results show that in text analysis, were found that characterize critical pedagogy. In the analysis of discourse practice, the critical pedagogy that emerges is only half-assed, not complete. As for sociocultural analysis, the results of the PISA ranking and the pandemic which caused an economic recession are the reasons why critical pedagogy did not fully emerged.